Analysis of the Quality of Student Administration Services at SMK PGRI Enrekang - Nasaruddin Hasyim; Muhammad Fadli; Haedar Akib (Asha Publishing, 2024)
Student administration plays an important role in the implementation of school activities to run effectively and efficiently. This study aims to determine the quality of student administration services at SMK PGRI Enrekang. This study is a qualitative descriptive study. The informants in this study were the Head of Administration, Teachers, and Students. Data collection techniques through observation, interview, and documentation methods. Data analysis techniques use data collection techniques, condensation, data presentation, and drawing conclusions. The results of the study indicate that the quality of student administration services at SMK PGRI Enrekang is in the